Hurricane Michael Altered the Structure and Function of Longleaf Pine Woodlands. Issue 12 (7th December 2021) - Kenney, G.; Staudhammer, C. L.; Wiesner, S.; Brantley, S. T.; Bigelow, S. W.; Starr, G.
Abstract: Tropical cyclones can physically alter ecosystems, causing immediate and potentially long‐lasting effects on carbon dynamics. In 2018, Hurricane Michael hit the southeastern United States with category 5 winds at landfall and category 2 winds reaching over 100 miles inland, resulting in extensive damage. Longleaf pine woodlands in the path of the hurricane were damaged, but severity varied based on the storm track. We used a combination of eddy covariance measurements, airborne LiDAR, and forest inventory data to determine whether hurricane affects structure, function, and recovery of two longleaf pine woodlands at the ends of an edaphic gradient. We found that the carbon sink potentials in both sites were diminished following the storm, with reductions in net ecosystem exchange (NEE) primarily due to lower rates of photosynthesis, as respiration only increased marginally. The xeric site carbon losses and physiological reductions were smaller following the disturbance, which led to the recovery of ecosystem physiological activity to prestorm rates before that of the mesic site, as indicated by maximum ecosystem CO2 uptake rates. Two years following the hurricane both stands continued to have reduced NEE, which signaled altered function. We expect both locations to recover their lost carbon stocks in ∼10–35 years; however, long‐term studies are needed to examine how longleaf woodlands respond to compounding disturbances, such as drought, fire, or other wind storms, which vary significantly across the ecosystem's range. Additionally, hurricanes are intensifying due to climate change, potentially amplifying the degree to which they will alter this ecosystem in the future. Plain Language Summary: Hurricane Michael hit the Northern Gulf of Mexico in October 2018, causing damage to ecosystems within its path. The Jones Center at Ichauway experienced damage to longleaf pine woodlands on the reserve. This damage ranged from removal of leaves and needles from the canopy, to snapped limbs and whole tree mortality. We studied the effects the hurricane had on the structure, physiology, and recovery of two longleaf sites, one with high soil water availability (mesic site) and one with lower soil water availability (xeric site). Both stands experienced declines in photosynthesis and increases in respiration, which reduced their carbon sequestration capacity. Two years following the storm, the sites are still recovering. Interestingly the xeric site was less affected by the storm due to the presence of shorter trees with larger root systems and lower tree densities, which are associated with soil water limitations at the site. We predict that it will take the sites ∼10–35 years to recover the carbon loss associated with this hurricane damage. Key Points: Hurricane Michael altered the structure and function of longleaf pine woodlands Ecological memory of water limitations led to less hurricane damage at our xeric site Carbon recapture at the two sites may take from 10 to 35 years